Lack of Rule-Adherence During Mountain Gorilla Tourism Encounters in Bwindi Impenetrable National Park, Uganda, Places Gorillas at Risk From Human Disease - Weber, Annalisa; Kalema-Zikusoka, Gladys; Stevens, Nancy J. (Frontiers in Public Health, 2020)
Mountain gorillas (Gorilla beringei beringei) are an endangered primate species, with 43% of the 1,063 individuals that remain on the planet today residing in Bwindi Impenetrable National Park (BINP) in southwestern Uganda. These primates are at the heart of a growing tourism industry that has incentivized their continued protection, but close proximity between humans and gorillas during such encounters presents well-documented risks for disease transmission. The Uganda Wildlife Authority (UWA) has developed rules to help protect the health of the gorillas, limiting each habituated gorilla group to a single 60 min visit each day by a group of no more than 8 tourists, and emphasizing that humans maintain a >7 m distance from gorillas at all times. A number of studies have documented that not all tour groups respect these rules. This project assesses rule-adherence during gorilla tourism encounters at BINP using both observational and survey-based data collected during the tourism high season between May and August, 2014. Observational data from 53 treks reveal that groups of 1–11 tourists engaged in gorilla viewing encounters between 46 and 98 min in duration. Although 96% of pre-trek briefings conducted by park rangers emphasized the need to maintain >7 m human-gorilla spacing, the 7 m distance rule was violated in over 98% (52 out of 53) of the tours examined in this study. Observational data were collected at 2 min intervals during gorilla-viewing encounters, documenting the nearest distance between any tourist and a gorilla (n = 1,604), of which 1,094 observations (68.2%) took place at a distance less than or equal to 7 m. Importantly, the 7 m rule was violated in visits to all of the gorilla groups habituated during the time of the study. In 224 observations ( 14%, per 1,604 total), human-gorilla spacing was 3 m or less. Survey data (n = 243) revealed promising opportunities to improve tourist understanding of and adherence to park rules, with 73.6% of respondents indicating that they would be willing to utilize a precautionary measure of wearing a face-mask during encounters to protect gorilla health.